Aspect Factor and Soil Erosion Vulnerability on Rural Livelihoods in Mubi North and Mubi South Local Government Areas of Adamawa State, Nigeria - K. A. Nnanguma (Journal of Applied Sciences and Environmental Management)
Aspect factor, which determines slope orientation, significantly influences soil moisture retention, vegetation cover, and erosion vulnerability. Hence, the objective of this paper was to assess the aspect factor and soil erosion vulnerability on rural livelihoods in Mubi North and Mubi South Local Government Areas of Adamawa State, Nigeria using a mixed-method approach was employed, integrating GIS-based analysis, remote sensing, field surveys, and socio-economic assessments. Data were collected from 1,000 respondents across 26 communities and analyzed using spatial mapping and statistical techniques. Findings indicate that south-facing slopes, such as those in Wuro Harde, Lokuwa, and Barama, experience higher erosion due to increased solar radiation and moisture loss, while shaded slopes in Gipalma and Kabang exhibit reduced vulnerability. Soil erosion significantly affects livelihoods by diminishing agricultural productivity, reducing pasture lands, and limiting commercial activities. The study contributes to knowledge by identifying high-risk erosion zones and providing insights for sustainable land management strategies. Recommendations include afforestation, improved agricultural practices, and policy interventions to mitigate erosion effects.